LGBTQI cancer patients’ quality of life and distress: A comparison by gender, sexuality, age, cancer type and geographical remoteness - Ussher, Jane M.; Allison, Kimberley; Perz, Janette; Power, Rosalie; , The Out with Cancer Study Team (Frontiers in Oncology, 2022)
Background: There is growing acknowledgement of the psycho-social vulnerability of lesbian, gay, bisexual, transgender, queer and/or intersex (LGBTQI) people with cancer. The majority of research to date has focused on cisgender adults with breast or prostate cancer. Study Aim: This study examined psycho-social factors associated with distress and quality of life for LGBTQI cancer patients and survivors, across a range of sexualities and gender identities, intersex status, tumor types, ages and urban/rural/remote location using an intersectional theoretical framework. Method: 430 LGBTQI people with cancer completed an online survey, measuring distress, quality of life (QOL), and a range of psycho-social variables. Participants included 216 (50.2%) cisgender women, 145 (33.7%) cisgender men, and 63 (14.7%) transgender and gender diverse (TGD) people. Thirty-one (7.2%) participants reported intersex variation and 90 (20%) were adolescents or young adults (AYA), aged 15-39. The majority lived in urban areas (54.4%) and identified as lesbian, gay or bisexual (73.7%), with 10.9% identifying as bisexual, and 10.5% as queer, including reproductive (32.4%) and non-reproductive (67.6%) cancers. Results: Forty-one percent of participants reported high or very high distress levels, 3-6 times higher than previous non-LGBTQI cancer studies. Higher rates of distress and lower QOL were identified in TGD compared to cisgender people, AYAs compared to older people, those who identify as bisexual or queer, compared to those who identify as lesbian, gay or homosexual, and those who live in rural or regional areas, compared to urban areas. Elevated distress and lower QOL was associated with greater minority stress (discrimination in life and in cancer care, discomfort being LGBTQI, lower outness) and lower social support, in these subgroups. There were no differences between reproductive and non-reproductive cancers. For the whole sample, distress and poor QOL were associated with physical and sexual concerns, the impact of cancer on gender and LGBTQI identities, minority stress, and lack of social support. Conclusion: LGBTQI people with cancer are at high risk of distress and impaired QOL. Research and oncology healthcare practice needs to recognize the diversity of LGBTQI communities, and the ways in which this minority stress and lack of social support may affect wellbeing.